UPAYA PELESTARIAN GERABAH TRADISIONAL MELALUI IMPLEMENTASI MESIN GERABAH ERGONOMIS DI DESA KAPAL MENGWI - I Ketut Widana; Ni Wayan Sumetri; I Made Rasta (Bhakti Persada Jurnal Aplikasi IPTEKS, 2019)
The business of traditional pottery, especially carat and coblong, has existed for a long time, said that since Hinduism began to be adopted by the Balinese. Carat is a ceremonial tool that has a design like a jug, only in small form, while coblong resembles a jar. In their use, both are filled with water, supplementing the fire and flowers which are usually always present at every Hindu prayer in Bali. Carat and coblong making technology is fairly traditional and has not been touched by modern technology. The manufacturing process, starting from the treatment of materials, the formation and finishing is done in a conventional way, which uses the feet and hands. The elements of skill and experience play an important role in the realization of carat and coblong pottery products. The aim of the program is to empower craftsmen by giving a touch of modern technology to work tools. The method used is socialization, provision of work tools, testing tools and data retrieval. The testing of the tool was assisted by 7 subjects who volunteered to be involved as testers. Data is taken twice, namely when the subject works using conventional work tools and when using ergonomic or modern work tools. The test results show that by using modern tools, subjects feel the reduction in pain due to work which in the long run will have implications for increasing the productive life of the craftsman and increasing productivity. Kata Kunci : gerabah, alat kerja ergonomis, sakit akibat kerja, produktivitas The business of traditional pottery, especially carat and coblong, has existed for a long time, said that since Hinduism began to be adopted by the Balinese. Carat is a ceremonial tool that has a design like a jug, only in small form, while coblong resembles a jar. In their use, both are filled with water, supplementing the fire and flowers which are usually always present at every Hindu prayer in Bali. Carat and coblong making technology is fairly traditional and has not been touched by modern technology. The manufacturing process, starting from the treatment of materials, the formation and finishing is done in a conventional way, which uses the feet and hands. The elements of skill and experience play an important role in the realization of carat and coblong pottery products. The aim of the program is to empower craftsmen by giving a touch of modern technology to work tools. The method used is socialization, provision of work tools, testing tools and data retrieval. The testing of the tool was assisted by 7 subjects who volunteered to be involved as testers. Data is taken twice, namely when the subject works using conventional work tools and when using ergonomic or modern work tools. The test results show that by using modern tools, subjects feel the reduction in pain due to work which in the long run will have implications for increasing the productive life of the craftsman and increasing productivity. Keywords: earthenware, ergonomic work tools, work-related illness, productivity